Sensory Neuropeptides and Endogenous Opioids Expression in Human Dental Pulp with Asymptomatic Inflammation: In Vivo Study - Daniel Chavarria-Bolaños; Hector Flores-Reyes; Nelson Lombana-Sanchez; Bernardino Cerda-Cristerna; Amaury Pozos-Guillen (Mediators of Inflammation)
Purpose. This study quantified the expression of substance P (SP), calcitonin gene-related peptide (CGRP), β-endorphins (β-End), and methionine-enkephalin (Met-Enk) in human dental pulp following orthodontic intrusion. Methods. Eight patients were selected according to preestablished inclusion criteria. From each patient, two premolars (indicated for extraction due to orthodontic reasons) were randomly assigned to two different groups: the asymptomatic inflammation group (EXPg), which would undergo controlled intrusive force for seven days, and the control group (CTRg), which was used to determine the basal levels of each substance. Once extracted, dental pulp tissue was prepared to determine the expression levels of both neuropeptides and endogenous opioids by radioimmunoassay (RIA). Results. All samples from the CTRg exhibited basal levels of both neuropeptides and endogenous opioids. By day seven, all patients were asymptomatic, even when all orthodontic-intrusive devices were still active. In the EXPg, the SP and CGRP exhibited statistically significant different levels. Although none of the endogenous opioids showed statistically significant differences, they all expressed increasing trends in the EXPg. Conclusions. SP and CGRP were identified in dental pulp after seven days of controlled orthodontic intrusion movement, even in the absence of pain.